Cognitive and neural markers of super-recognisers' face processing superiority and enhanced cross-age effect. (November 2018) - Belanova, Elena; Davis, Josh P.; Thompson, Trevor
Abstract: Super-recognisers inhabit the extreme high end of an adult face processing ability spectrum in the population. While almost all research in this area has evaluated those with poor or mid-range abilities, evaluating whether super-recognisers' superiority generates distinct electrophysiological brain activity, and transcends to different age group faces (i.e., children's) is important for enhancing theoretical understanding of normal and impaired face processing. It may also be crucial for policing, as super-recognisers may be deployed to operations involving child identification and protection. In Experiment 1, super-recognisers ( n  = 315) outperformed controls ( n  = 499) at adult and infant face recognition, while also displaying larger cross-age effects. These findings were replicated in Experiment 2 (super-recognisers, n  = 19; controls, n  = 28), although one SR with frequent infant exposure showed no cross-age effect. Compared to controls, super-recognisers also generated significantly greater electrophysiological activity in event-related potentials associated with pictorial processing (P1) and explicit recognition (P600). Experiment 3, employing an upright and inverted sequential matching design found super-recognisers ( n  = 24) outperformed controls ( n  = 20) at adult and infant face matching, but showed no upright cross-age matching effects. Instead, they displayed larger inversion effects, and cross-age inversion effects, implicating the role of holistic processing in their perceptual superiority. Larger cross-age effects in recognition, but not matching suggests that super-recognisers' adult face recognition is partly driven by experience. However, their enhanced infant face recognition suggest super-recognisers' superiority is also experience-independent, results that have implications for policing and for models of face recognition.